Preserving Pancasila Through Values and Character in Cultural Citizenship of Plural Communities - Giri Harto Wiratomo; Dadang Sundawa; Natal Kristiono; Edwindha Prafitra Nugraheni (Universitas PGRI Kanjuruhan Malang, 2025)
This research is based on the importance of civic culture by maintaining Pancasila values. The uniqueness of this research is the practice of civic culture in the village to maintain Pancasila values through Pancasila conservation. One of the villages that maintains this citizenship culture is the Genting village, Semarang district, Central Java province. The purpose of this research is to explore the culture of citizenship in the Genting community as a form of conserving Pancasila values, supporting and inhibiting factors, as well as efforts made to preserve Pancasila values as a civic culture. The research method used is qualitative with a phenomenological approach. Retrieval of research data using observation, in-depth interviews, Forum Group Discussion, and documentation. The results and discussion of this study are the practice of citizenship culture by conserving Pancasila values, which means caring for, maintaining and maintaining Pancasila values. The good practice of civic culture in the multicultural community of Genting Village, namely the citizenship tradition as a socio-cultural action by preserving the citizenship culture through agro-tourism, cultural tourism, culinary tourism, and spiritual tourism.